2020
DOI: 10.1371/journal.pone.0226062
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of and interest in HIV pre-exposure prophylaxis use among adolescent girls and young women in Lilongwe, Malawi

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
6
26
0
Order By: Relevance
“…Whereas the current literature on integrated PrEP-FP delivery often refers to “FP clinics” as a uniform delivery setting, our study revealed key points of heterogeneity between two FP clinics that influenced implementation (e.g., organizational mission, clinic flow). Our finding that the youth-friendly clinic was potentially “low-hanging fruit” for this HIV prevention innovation is consistent with other projects and programs in Kenya [ 6 ], South Africa [ 33 , 34 ], and Malawi [ 35 ], which similarly reported that providers at these venues were generally open to delivering PrEP and that AGYW like obtaining services in these settings. The implications of our findings for scale-up are even clearer when placed within the context of a typology of health facilities recently developed by Dunbar et al based on their assessment of 20 facilities in Kenya and Zimbabwe [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Whereas the current literature on integrated PrEP-FP delivery often refers to “FP clinics” as a uniform delivery setting, our study revealed key points of heterogeneity between two FP clinics that influenced implementation (e.g., organizational mission, clinic flow). Our finding that the youth-friendly clinic was potentially “low-hanging fruit” for this HIV prevention innovation is consistent with other projects and programs in Kenya [ 6 ], South Africa [ 33 , 34 ], and Malawi [ 35 ], which similarly reported that providers at these venues were generally open to delivering PrEP and that AGYW like obtaining services in these settings. The implications of our findings for scale-up are even clearer when placed within the context of a typology of health facilities recently developed by Dunbar et al based on their assessment of 20 facilities in Kenya and Zimbabwe [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…PrEP is an important prevention option for AGYW, providing an opportunity for greater autonomy and control over sexual health. 22 Recent PrEP studies and our findings underscore the need for approaches to support PrEP initiation and adherence to PrEP during periods of use, 23 particularly among the many women in our study who reported condom-less sex. Stigma, norms and sexual partners have been shown to influence PrEP use and adherence.…”
Section: Discussionmentioning
confidence: 53%
“…Reinforcing ART adherence strategies would positively contribute to the reduction of HIV transmissions. Similarly, pre-exposure prophylaxis is another emerging biomedical strategy that can be promoted in SSA to benefit sexual partners who are HIVnegative (Maseko et al, 2020, Zimba et al, 2019.…”
Section: Discussionmentioning
confidence: 99%